A Perspective on Proteomics of Infectious Diseases. Issue 4 (19th January 2018) - Venkatesh, Apoorva; Gil, Concha; Fuentes, Manuel; LaBaer, Joshua; Srivastava, Sanjeeva
Abstract: Pneumonia, HIV/AIDS, tuberculosis, malaria and several other diseases caused by pathogens largely contribute to the enormous burden of infectious diseases. Over the last few decades, the impact of infectious diseases on a population has been drastic and remains a major health concern even today. Despite advances in science and technology in this era of health and development, there is a substantial knowledge gap in our understanding of the molecular basis of these infectious diseases. The availability of valuable genomic information for a number of pathogens and their hosts has improved our understanding of disease pathogenesis but has not always been useful in addressing important biological questions. The primary reason lies in the fact that genes do not best reflect the status of a cell. Proteins represent the functional molecules of a cell and are ultimately responsible for controlling most aspects of cellular function. Their existence as different isoforms owing to posttranslational modifications suggests that many proteins can be produced by the same gene. Furthermore, not all mRNAs are translated at all times justifying the need to develop additional tools to study proteins as separate molecular entities. Their presence or absence under disease conditions, varying levels, different forms, and functions need to be carefully studied to understand molecular alterations in response to a disease. Here, we describe the applications of proteomics‐based approaches to study infectious diseases with a note on the objectives of the Human Proteome Project (HPP)‐Human Infectious Diseases (HID) project under the HUPO's flagship program.